2022
DOI: 10.1093/pm/pnac153
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Blocks as a Predictor for Response to Ketamine Infusion in Patients with Complex Regional Pain Syndrome: A Multicenter Study

Abstract: Background Ketamine infusions are frequently employed for refractory complex regional pain syndrome (CRPS), but there are limited data on factors associated with treatment response. Sympathetic blocks are also commonly employed in CRPS for diagnostic and therapeutic purposes, and generally precede ketamine infusions. Objectives We sought to determine whether demographic and clinical factors, and technical and psychophysical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There are several reasons why the patient may have experienced prolonged relief of pruritus. For pain, a morphological and teleological cousin to itch, the most commonly cited reason for relief that outlasts the pharmacological duration of action for ketamine is the reversal of central sensitization . Additionally, prolonged effects of local anesthetic blockade have been anecdotally described, which are possibly associated with reversing peripheral and central sensitization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reasons why the patient may have experienced prolonged relief of pruritus. For pain, a morphological and teleological cousin to itch, the most commonly cited reason for relief that outlasts the pharmacological duration of action for ketamine is the reversal of central sensitization . Additionally, prolonged effects of local anesthetic blockade have been anecdotally described, which are possibly associated with reversing peripheral and central sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…For pain, a morphological and teleological cousin to itch, the most commonly cited reason for relief that outlasts the pharmacological duration of action for ketamine is the reversal of central sensitization. 6 Additionally, prolonged effects of local anesthetic blockade have been anecdotally described, which are possibly associated with reversing peripheral and central sensitization. One limitation is that because the patient was from out of state and infusions are rarely covered by payers, effectiveness (practicality) was prioritized vs diagnostic/mechanistic and efficacy considerations by using 3 treatments at high doses, thereby limiting the conclusions that could be drawn about individual therapies.…”
Section: Ketamine Infusions For Treatment-resistant Neuropathic Pruritusmentioning
confidence: 99%
“…We also investigated whether outcomes of sympathetic nerve blocks can predict responders of spinal cord stimulation and found that there was no difference in the success rate of spinal cord stimulation trials between patients with or without more than 50% pain relief after sympathetic blocks (35 of 40, 88% vs. 26 of 29, 90%, P > 0.990) (86). In a multicenter study, we further investigated the demographic and clinical factors of sympathetic blocks as a predictor for response to ketamine infusion, a treatment frequently used in clinical practice (87), in patients with CRPS (80,87). Factors associated with a positive response to ketamine in univariable analysis were the presence of sympathetically mediated pain (SMP) [61.0% success rate vs. 26.7% in those with sympathetically independent pain (SIP); P = .009] and post-block temperature increase (5.66 ± 4.20 in ketamine responders vs. 3.68 ± 3.85 in non-responders; P = .043).…”
Section: Autonomic Dysfunctionmentioning
confidence: 98%
“…In addition, sympatho-afferent coupling can be explained by increased expression of adrenergic receptors on nociceptive fibers following injury. Hence sympathetic activation induces nociceptive fibers causing increased pain in most patients with CRPS (33,80). Elevated sympathetic nervous system activity may amplify spontaneous pain by 22%.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…The cognitive-evaluative component takes into account catastrophizing, fear-avoidance, insight into one’s condition and past experiences, and can be quantified using questionnaires such as the Pain Catastrophizing Scale 10. Individuals with higher affective pain components (eg, pain worsened by anxiety) may respond better to antidepressants and ketamine,11 while those whose pain beliefs are grounded in misconceptions and poor insight may benefit from cognitive-behavioral therapy (CBT).…”
Section: Overview Of Painmentioning
confidence: 99%